Noise, vibration and harshness during dry clutch engagement oscillations. (December 2020) - Minas, I; Morris, N; Theodossiades, S; O'Mahony, M
Determining the root causes of various noise, vibration and harshness phenomena in modern automotive drivetrains is a critical task for industry, since noise, vibration and harshness issues often result in worsened driving experience. The aim of the current research is to investigate the dynamics during dry clutch engagement and the associated – often problematic – oscillations. This paper reports the development and partial validation of numerical models to study dry clutch behaviour. The models are used to investigate the influence of clutch and throttle actuation on the occurrence of unwanted clutch oscillations. The dynamic coefficient of friction between the clutch interacting surfaces was measured using a pin-on-disc rig under different slip speeds and contact pressure conditions, which are representative of a typical clutch engagement manoeuvre. The paper highlights the occurrence of instability issues in clutch dynamics (disc radial mode) as potential generators of aggressive noise, vibration and harshness, particularly during two different clutch pedal actuations. Such analysis has not hitherto been reported in the open literature.